+0  
 
0
395
2
avatar

Why does (-7) to the zero power minus 7 to the zero power equal zero when (-7) to the zero power equals -1 and 7 to the zero power equals 1... the equation would be -1-1= -2 but when i put it in a calculator it equals 0 can you please explain?

 Jun 30, 2019
 #1
avatar
+1

Both (-7)^0 and 7^0 =1. It is NOT true that -7^0 = -1.

Since both =1, then 1 - 1 = 0. And that is it.

 Jun 30, 2019
 #2
avatar+21631 
+2

The reason why your calculator evaluate  -70  as  -1  is because, for the calculator, it is evaluated as  -(70),  which is  -(1)  =  -1.

If you wanted it to be evaluated as  (-7)0,  which is  1,  you will need to include the parentheses.

 Jun 30, 2019

9 Online Users

avatar
avatar